EFEKTIFITAS PROGRAM PENDAMPINGAN DESA WISATA DI DESA BEJIJONG KABUPATEN MOJOKERTO - Novianto Edi Suharno; M. Nilzam Aly; Bambang Suharto; Sri Endah Nurhidayati (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2020)
Ideally, community empowerment programs in rural areas should not be implemented once in a while. This is very important to maintain the aspect of sustainability and achieve the goals maximally. People in rural areas are the target of empowerment programs considering the many problems that exist there. Statistical data shows that the distribution of the majority of the national poor is in rural areas. One method of reducing poverty is through the development of tourist villages. The purpose of the tourism village assistances are to increase the understanding and skills of the community in Bejijong Tourism Village, especially in the field of homestay management and online marketing of citizen handicraft products. The stages in this empowerment program through three methods, namely preparation, implementation, and evaluation. The research method used is qualitative with data collection methods through observation, interviews, focus group discussions, and filling out questionnaires. The results of this activity indicate that the understanding and competence of citizens has increased for the better. The results of this activity were measured using a questionnaire (pre-test and post-test) and calculated using a Likert scale.